2012
DOI: 10.1097/aog.0b013e31826bb121
|View full text |Cite
|
Sign up to set email alerts
|

Management of Endometrial Precancers

Abstract: In the United States, endometrial cancer is the most commonly diagnosed cancer of the female reproductive system. Strategies to sensitively and accurately diagnose premalignant endometrial lesions are sorely needed. We reviewed studies pertaining to the diagnostic challenges of endometrial precancers, their predictive value, and evidence to support management strategies. Currently, two diagnostic schema are in use; the 4-class WHO94 hyperplasia system, based on morphologic features of architectural complexity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
83
2
21

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(112 citation statements)
references
References 73 publications
2
83
2
21
Order By: Relevance
“…The true incidence of the various types of endometrial hyperplasia in the general population is unknown; the estimated prevalence is as high as 132 per 100 000 woman‐years [3]. Many classification systems for endometrial hyperplasia have been described over the past 60 years [4]. The most widely used is the WHO 1994 classification system, which is largely based on a study by Kurman et al [5] published in 1985 that correlated cytologic atypia with the risk for endometrial cancer in 170 patients with endometrial hyperplasia who were followed up for at least 12 months [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The true incidence of the various types of endometrial hyperplasia in the general population is unknown; the estimated prevalence is as high as 132 per 100 000 woman‐years [3]. Many classification systems for endometrial hyperplasia have been described over the past 60 years [4]. The most widely used is the WHO 1994 classification system, which is largely based on a study by Kurman et al [5] published in 1985 that correlated cytologic atypia with the risk for endometrial cancer in 170 patients with endometrial hyperplasia who were followed up for at least 12 months [6].…”
Section: Resultsmentioning
confidence: 99%
“…For women with endometrial hyperplasia or low‐grade, well‐differentiated endometrioid‐type endometrial cancer for whom a conservative approach is being considered, tissue samples must be reviewed by an expert pathologist. There is insufficient evidence to recommend endometrial sampling via dilatation and curettage over office Pipelle biopsy [4]. The rates of cancer detection in women with abnormal uterine bleeding are similar with either curettage or Pipelle sampling, and in as many as 60% of curettages, less than half of the endometrium is sampled [33,34].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, pathological diagnosis is limited by both over-and under-estimation of disease severity, leading to over-treatment of some women and delayed diagnosis of others. [8][9][10] Given that the incidence of endometrial carcinoma and its precursors may rise in future years, likely reflecting dramatic increases in the prevalence of obesity, 34 a strong endometrial carcinoma risk factor, improved methods for triaging women according to risk may having growing utility.…”
Section: Discussionmentioning
confidence: 99%
“…8 Data suggest that community pathologists over-diagnose endometrial hyperplasia compared with experts, 8 but 40% of biopsies reported as atypical endometrial hyperplasia, even on review, are associated with prevalent carcinoma at hysterectomy. 9,10 We propose that the development of a molecular test that could aid in the management of abnormal vaginal bleeding could enable triage of patients with carcinoma, while reducing over-treatment of innocuous lesions. Among women with limited health care access, rapid identification of carcinomas may increase chances of cure and reduce the need for more aggressive treatment secondary to disease progression, whereas ruling out high-risk lesions could allow many women to safely opt for conservative management.…”
mentioning
confidence: 99%
“…Hysterectomy is usually the treatment of choice if a woman has decided not to have any more children. Young patients wishing to preserve their fertility and women who are poor surgical candidates may be treated with oral progestins or hormonal intrauterine devices [4,21]. Treatment with systemic progestins can successfully ablate up to 90% of endometrial precancers in young women [22].…”
Section: Discussionmentioning
confidence: 99%